Penerapan Standar Operasional Prosedur Pelaksanaan Izin Dan Retribusi Pemotongan Pepohonan Di Kabupaten Lumajang - Fitri Anggraeni; Dewita Sari; Mariya Ulfa (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to analyze and evaluate the application of Standard Operating Procedures (SOP) in the implementation of permits and levies for cutting trees in Lumajang Regency. The research method used is a case study with a qualitative approach. Data was collected through in-depth interviews with relevant stakeholders as well as analysis of documents related to applicable regulations and SOPs. The research results show that the application of SOPs in implementing permits and levies for cutting trees still has several shortcomings and challenges. This research also provides recommendations for further improvement and development in implementing the SOP.